2020
DOI: 10.21037/atm.2020.01.107
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pathological complete response in rectal cancer after chemoradiotherapy with a random forest using 18F-fluorodeoxyglucose positron emission tomography and computed tomography radiomics

Abstract: Background: Neoadjuvant chemoradiotherapy (NCRT) followed by surgery is the standard treatment for patients with locally advanced rectal cancer. This study developed a random forest (RF) model to predict pathological complete response (pCR) based on radiomics derived from baseline 18 F-fluorodeoxyglucose ([ 18 F] FDG)-positron emission tomography (PET)/computed tomography (CT).Methods: This study included 169 patients with newly diagnosed rectal cancer. All patients received 18 F[FDG]-PET/CT, NCRT, and surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…We collected 47 publications on “Other” cancer types. This category included studies on gastrointestinal (11) [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 ], pancreatic (8) [ 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 ], sarcoma (8) [ 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 ], neuroendocrine (5) [ 284 , 285 , 286 , 287 , 288 ], prostate (4) [ 289 , 290 , 291 , 292 ], thyroid (3) [ 293 , 294 , 295 ], thymic (2) [ 296 , 297 ], skin (2) [ 298 , 299 ], liver (2) [ 300 , 301 ], and renal carcinomas (1) [ 302 ]. The average number of patients was 84 (median = 70, range, 26–214) and the average number of textural features extracted was 29 (median = 17, ...…”
Section: Resultsmentioning
confidence: 99%
“…We collected 47 publications on “Other” cancer types. This category included studies on gastrointestinal (11) [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 ], pancreatic (8) [ 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 ], sarcoma (8) [ 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 ], neuroendocrine (5) [ 284 , 285 , 286 , 287 , 288 ], prostate (4) [ 289 , 290 , 291 , 292 ], thyroid (3) [ 293 , 294 , 295 ], thymic (2) [ 296 , 297 ], skin (2) [ 298 , 299 ], liver (2) [ 300 , 301 ], and renal carcinomas (1) [ 302 ]. The average number of patients was 84 (median = 70, range, 26–214) and the average number of textural features extracted was 29 (median = 17, ...…”
Section: Resultsmentioning
confidence: 99%
“…This method has recently gained attention as a promising tool for predicting prognosis and guiding clinical decision-making (17,18). Recent studies on rectal cancer have provided encouraging evidence that radiomics can be applied to predict characteristics including therapeutic responses (19,20), lymph node metastasis (21,22), and KRAS mutations (23,24). Three recent studies, including all left-and right-sided colorectal cancers, reported that radiomics analysis based on computed tomography (CT) data could predict MSI in colorectal cancer (25)(26)(27); however, MSI prevalence in colorectal cancer is not evenly distributed, and it gradually varies from the proximal colon to the rectum (28).…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate the introduction of a practical prediction model, we conducted analyses on the basis of random forest analysis and Lasso analysis to retrieve the intersected proportion for dimensionally reduction and features selection, which has been widely used for characteristics of cancer diagnosis and therapy [24][25][26]. After this group of genes identified, the respective prediction values for pCR were successively evaluated by logistic analysis, and the six-gene panel comprising ATP4B, FBXO22, FCN2, RRP8, SMERK2, TET3 were finally recognized.…”
Section: Discussionmentioning
confidence: 99%